Revisiting the 40,000 BP crisis in Iberia - Camps Calbet, M (2004)
This thesis focuses on the Mid/Upper Palaeolithic Transition in the Iberian Peninsula, and questions whether this process took place as hitherto widely claimed, by testing the validity of the traditional characteristics said to portray this event throughout Europe. Research was carried out at different levels: old archaeological collections from two transitional sites (Abric Romani and Reclau Viver), previously unstudied, were systematically analysed and specific organic components (perforated shells) were radiocarbon dated. A thorough bibliographic database including information on these and all other Iberian sites was complied, in order to extend the study. The theoretical perspective of the topic was also investigated, to assess epistemological factors which are so often overlooked in this field of study. The socio-political events that have marked Spain and Portugal's contemporary histories, were also studied, since they played a crucial role in shaping Palaeolithic Research in both countries. The so-called '40,000 BP Crisis', specifically located in northern Iberia, was revisited by studying not only the traditional sites which have produced chronometric readings around that date, but also others in the same region whose transitional layers have yielded much younger dates, to see if that phenomenon really existed or has been created by generalisations that have masked vital - but ultimately uncomfortable - information. The study of this event is also placed into the peninsular and the wider European contexts, an exercise that has disclosed the vast complexity of the Transition, in terms of both the actual archaeological record and the theoretical interpretations that have been presented so far. Ultimately, this research calls for a revision of some of the theoretical perspectives of Palaeolithic archaeologists, as well as far more careful site and regional-level research, in order to redress the abundant misconceptions that distort our understanding of the Transition process.